Trends and Evolution of Data-Driven Financial Management: A Bibliometric Analysis of Scientific Publications and Their Influence on Financial Decision Making - Judijanto, Loso; Devi, Erwina Kartika; Yusuf, Syarifuddin (Westscience Press, 2023)
The field of data-driven financial management has witnessed a dynamic evolution, marked by interdisciplinary collaborations, technological advancements, and a surge in research output. This bibliometric analysis explores the landscape of scholarly publications, clustering works into thematic groups, identifying influential authors, and examining prevalent terms. Clusters reveal diverse focuses, including business models, artificial intelligence, optimization, and predictive modeling. Influential works by McAfee et al., Wu et al., and Gómez-Bombarelli et al. underscore the intersection of big data, analytics, and innovative applications in chemistry. The distribution of publication years indicates a recent upswing in research activity, aligning with the rapid advancements in data science. Term occurrences highlight the central role of